Comparison of soybean oil- and olive oil-based lipid emulsions on hepatobiliary function and serum triacylglycerols level during realimentation - Pálová, Sabina; Charvát, Jiří; Kvapil, Milan (Journal of international medical research, 2008)
This study compared the effects of soybean oil- versus olive oil-based lipid emulsions on hepatobiliary function and serum triacylglycerols in patients who required transient parenteral nutrition support for significant weight loss. Patients who received a parenteral ready-to-use industry admixture including either soybean oil- (n = 10) or olive oil-based lipid emulsion (n = 11) for 2 weeks were retrospectively analysed. Cholestatic and cytolytic enzymes, conjugated bilirubin and serum triacylglycerols were sampled before and 1 day after completing parenteral nutrition support. Significant deterioration of cholestatic enzymes occurred in five patients in the soybean oil group and in one in the olive oil group. Serum triacylglycerols significantly deteriorated in seven patients in the soybean oil group and in one patient in the olive oil group. No differences were recorded for cytolytic enzyme abnormalities. In conclusion, the olive oil-based emulsion induced abnormalities of cholestatic enzymes and serum triacylglycerols significantly less frequently than the soybean oil-based emulsion.
Keywords: sójový olej; stravovací zvyklosti; Soybean Oil; jaterní testy; Feeding Behavior; Humans; lidé; hmotnostní úbytek; Fat Emulsions, Intravenous; lidé středního věku; Middle Aged; Female; Male; parenterální výživa; mužské pohlaví; Plant Oils; Biliary Tract; játra; ženské pohlaví; triglyceridy; Liver; Weight Loss; Parenteral Nutrition; tukové emulze intravenózní; Triglycerides; žlučové ústrojí; oleje rostlin; Liver Function Tests